2016
DOI: 10.4103/2230-8210.192924
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of depression and anxiety in patients of diabetes mellitus in a tertiary care center

Abstract: Background:Diabetes is one of the most common chronic diseases and affects virtually every organ of the human system. Depression and anxiety is common among patients with diabetes and associated with worse diabetes outcomes.Aims and Objective:To study the prevalence and predictors of depression and anxiety in patients of Type 2 diabetes mellitus (T2DM) in Pt. B.D. Sharma, PGIMS, Rohtak, Haryana, India, a tertiary care center in Northern India.Materials and Methods:Four hundred ten consecutive patients having T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
5
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 20 publications
6
49
5
4
Order By: Relevance
“…9 A study by Rajesh Rajput et al showed that depression and anxiety symptoms were two-fold higher in diabetic patients as compared to healthy controls. 10 In a population-based study in Chennai, it was found that the prevalence of depression was 23.4%. 11 Raval et al found a very high prevalence (41%) of depression in 300 patients with type 2 diabetes in a tertiary care hospital in Northern India.…”
Section: Discussionmentioning
confidence: 99%
“…9 A study by Rajesh Rajput et al showed that depression and anxiety symptoms were two-fold higher in diabetic patients as compared to healthy controls. 10 In a population-based study in Chennai, it was found that the prevalence of depression was 23.4%. 11 Raval et al found a very high prevalence (41%) of depression in 300 patients with type 2 diabetes in a tertiary care hospital in Northern India.…”
Section: Discussionmentioning
confidence: 99%
“…En el presente estudio, se comprobó que los portadores de DM 2 con sintomatología depresiva demuestran una menor adherencia farmacológica y un mayor nivel de descompensación metabólica, hallazgos consistentes con la literatura internacional [8][9][10]12,17,18,21,22,[25][26][27][28] pero que han sido estudiados escasamente a nivel nacional, pese a su relevancia como problemáticas de salud pública. De esta manera, puede abrirse camino a futuras investigaciones que contemplen otros pilares terapéuticos en DM 2 y depresión, con diseños metodológicos que permitan controlar los factores de confusión, y, posiblemente, demostrar relaciones de causalidad.…”
Section: Discussionunclassified
“…Así, existe evidencia contundente acerca de una prevalencia más alta de síntomas depresivos y trastorno depresivo mayor en los pacientes con DM 2 . No obstante, estas cifras varían según etnia [13][14][15] , rango etario 16,17 , lugar de residencia y nivel socioeconómico 18 .…”
unclassified
“…Among the 268 literatures retrieved, a total of 20 independent studies as well as a total of 19 had been incorporated in line with the inclusion and exclusion criteria of literature by use of the blind method [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. These included 3 articles about type I diabetes, 12 about type II diabetes, 5 about types I and II; and 1 article studied the types I and II diabetes independently (Figure 1).…”
Section: Characteristics Of Literatures Includedmentioning
confidence: 99%